Determinan Ekspor Kelapa Sawit di Indonesia Berdasarkan Data Tahun 2013-2023 - Mohammad Zainal Ruchban; Syafira Rizki Arsyad; Eva Alfiyana (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Export activities carried out by business actors are very important to be considered and carried out because they have a direct impact on the development of Indonesia. The purpose of this study is to analyze the factors that influence the value of palm oil exports. The method utilized for this research is descriptive quantitative which is then analyzed by utilizing multiple linear regression analysis through SPSS with the results presented descriptively. All data used in this study comes from publication data or secondary data that has been documented from 2013-2023. Then the technique in obtaining data through documentation techniques because the whole is obtained from data that has been published in general. For this reason, from the results of the analysis carried out, the overall conveys that the export value is influenced by the amount of production, the exchange rate of a currency and inflation indicated by 0.035 <0.05. The production factor of 0.010 <0.05 and the exchange rate of 0.009 <0.05 so that both have a significant effect and the factor of inflation 0.647>0.05 has no influence on the value of palm oil exports. Overall, it is conveyed that it has a significant effect on the value of palm oil exports. Then from the results of the study 68.6% the value of exports generated is directly influenced by these three factors